Anchorage of composite dowels. Issue 2 (May 2016) - Classen, Martin; Hegger, Josef
Abstract: In steel‐concrete composite beams, lifting effects between the steel section and the concrete slab usually occur incidentally and have comparatively small load ordinates compared with the shear forces transferred. For this reason, lifting forces are generally irrelevant for the dimensioning of the composite joint. Nevertheless, this statement does not apply if shear connectors are used for the systematic anchorage of pull‐out forces. Although the anchorage behaviour of conventional shear connectors, e.g. headed studs, has already been studied extensively, appropriate investigations into the anchorage behaviour of concrete composite dowels are lacking, especially for composite dowels in slender or cracked concrete slabs. In this paper, the anchorage behaviour of a puzzle‐shaped concrete composite dowel is investigated in cracked and uncracked concrete. To this end, particular test setups were developed. All tests were simulated using a three‐dimensional, non‐linear finite element model. Finally, an engineering model for calculating the anchoring capacity of single composite dowels and composite dowel groups in reinforced and unreinforced concrete is presented.